Pengaruh Supervisi Akademik Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru - Niatama, Normareta; Indriayu, Mintasih; Sukmayadi, Dodi (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this study was to analyze the effect of the principal's academic supervision on the performance of 21st Century Elementary School teachers in Tirtomoyo District. To analyze the effect of work motivation on the performance of 21st Century Elementary School teachers in Tirtomoyo District. To analyze the effect of the principal's academic supervision and work motivation simultaneously on the performance of 21st Century Elementary School teachers in Tirtomoyo District. The place of research was carried out at the Regional Coordinator for Education, Tirtomoyo, having its address at Jalan Mangga IV, RT 05 RW IX, Tirtomoyo District, Wonogiri Regency. the population in this study were 122 teachers. The sample used was 92 teachers. Data collection techniques with questionnaires. Data analysis technique with multiple linear regression. The results showed that the principal's academic supervision (X1) had a significant effect on teacher performance (Y). Work motivation (X2) has a significant effect on teacher performance (Y). Principal's academic supervision and work motivation have a joint effect on teacher performance.